2007
DOI: 10.5714/cl.2007.8.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Effect for TiO2/ACF Composite Electrochemically Prepared with TNB Electrolyte

Abstract: TiO 2 /ACF composites were prepared by the electrochemical method with Titanium (IV) n-butoxide (TNB) electrolyte under different electrochemical operation time. The BET surface area for TiO 2 /ACF composites decrease with the increase of electrochemical operation time. There is a single crystal structure which is anatase in all of the samples from the data of XRD. The SEM micrphotographs of TiO 2 /ACF composites show that the TiO 2 particles were well mixed with the ACF. There are O and P with strong C and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Uddin et al have studied the influence of TiO 2 and ZnO photocatalysts on adsorption and degradation behaviour of Erythrosine. 13) The photocatalytic activity for degradation of methyl orange using the nanosized TiO 2 /ZnO composite catalyst has been reported by Liao et al 14) In previous works, 15,16) it was found that TiO 2 /ACF composite has excellent photocatalytic activity in the degradation of methyl blue (MB), which is a representative azo dye. However, the influences of ZnO on photocatalyst TiO 2 /ACF in the degradation of MB, and the effect of ZnO on the photocatalytic activity of TiO 2 /ACF, are not known well.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Uddin et al have studied the influence of TiO 2 and ZnO photocatalysts on adsorption and degradation behaviour of Erythrosine. 13) The photocatalytic activity for degradation of methyl orange using the nanosized TiO 2 /ZnO composite catalyst has been reported by Liao et al 14) In previous works, 15,16) it was found that TiO 2 /ACF composite has excellent photocatalytic activity in the degradation of methyl blue (MB), which is a representative azo dye. However, the influences of ZnO on photocatalyst TiO 2 /ACF in the degradation of MB, and the effect of ZnO on the photocatalytic activity of TiO 2 /ACF, are not known well.…”
Section: Introductionmentioning
confidence: 87%
“…The result is in accordance with references. 15,16) However, for the Zn-treated ACF/TiO 2 composites, the peaks at 25.3, 37.8, 48.0 and 62.5 are the diffractions of (101), (004), (200) and (204) planes of anatase, indicating the developed CNT/TiO 2 composites existed in anatase state. The peaks at 27.4, 36.1, 41.2 and 54.3 belong to the diffraction peaks of (110), (101), (111) and (211) of rutile.…”
Section: Photocatalytic Decompositionmentioning
confidence: 99%
“…In order to investigate the efficiency of the CDP, indoor experiments were carried out by a static measurement, through the comparison of pure nano-TiO 2 and CDP crosslinking the same pure nano-TiO 2 with different particle sizes, nano-TiO 2 contents and test environments of light sources, NO 2 concentrations, temperatures, humidity and illuminance [10,22,23]. All the measurements implemented the standards of HJ479-2009 regulated by the Chinese Ministry of Environmental Protection.…”
Section: Photocatalytic Degradation Effectiveness Of the Cdpmentioning
confidence: 99%
“…A tremendous number of works on TiO 2 modification to improve its efficiency have been carried out in various ways, which include impurity doping [5,6], sensitization [7,8], surface modification [9], and fabrication of composites with other materials [10,11]. Activated carbon fiber (ACF), widely used as an effective adsorbent in treating polluted water and gas, has been introduced as a support for TiO 2 photocatalyst in some studies [12,13]. ACFs are one kind of highly microporous carbon materials, having a higher surface area, larger pore volume and a more uniform micropore size distribution than granular activated carbon [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%